Physiological Role of β-Phosphoglucomutase in Lactococcus lactis - Levander, Fredrik (American Society for Microbiology, 2001)
A β-phosphoglucomutase (β-PGM) mutant of Lactococcus lactis subsp. lactis ATCC 19435 was constructed using a minimal integration vector and double-crossover recombination. The mutant and the wild-type strain were grown under controlled conditions with different sugars to elucidate the role of β-PGM in carbohydrate catabolism and anabolism. The mutation did not significantly affect growth, product formation, or cell composition when glucose or lactose was used as the carbon source. With maltose or trehalose as the carbon source the wild-type strain had a maximum specific growth rate of 0.5 h(−1), while the deletion of β-PGM resulted in a maximum specific growth rate of 0.05 h(−1) on maltose and no growth at all on trehalose. Growth of the mutant strain on maltose resulted in smaller amounts of lactate but more formate, acetate, and ethanol, and approximately 1/10 of the maltose was found as β-glucose 1-phosphate in the medium. Furthermore, the β-PGM mutant cells grown on maltose were considerably larger and accumulated polysaccharides which consisted of α-1,4-bound glucose units. When the cells were grown at a low dilution rate in a glucose and maltose mixture, the wild-type strain exhibited a higher carbohydrate content than when grown at higher growth rates, but still this content was lower than that in the β-PGM mutant. In addition, significant differences in the initial metabolism of maltose and trehalose were found, and cell extracts did not digest free trehalose but only trehalose 6-phosphate, which yielded β-glucose 1-phosphate and glucose 6-phosphate. This demonstrates the presence of a novel enzymatic pathway for trehalose different from that of maltose metabolism in L. lactis.